The modifications of protective gear, rules and regulations during Taekwondo's evolution - From its obscure origins to the olympics - Moenig, U.; Cho, S; Song, H. (The International Journal of the History of Sport, 2012)
Asian martial arts were largely unknown until the 1960s in the Western world. Initially, taekwondo was mainly an outgrowth of Japanese karate, but later changed its fundamental character from a martial art for self-defence into a sport with the introduction of full-contact competitions. This also paved the way for taekwondo to eventually become an internationally recognised sport, in spite of the fact that originally this transformation was very controversial among the early taekwondo leaders and represented ultimately the outcome of their political struggles. Furthermore, the principle rules and regulations selected for the competition format had a profound effect on the technical direction of the sport. Rule changes and the improvement of protective equipment continued to play an important role in the shaping of taekwondo. The ongoing changes in the competition format, largely initiated by outside criticism and the fear of losing its Olympic membership status, are going to decide taekwondo's future direction and survival as a sport.